The Effect of Production Room Layout and Production Machine Maintenance on Production Effectiveness - Muhammad Herdiansyah (Almana : Jurnal Manajemen dan Bisnis, 2020)
The intense business competition in the industrial world requires companies to always advance. Many ways did so that companies can more effective in all fields so that company productivity can increase. In relation, the Production Room Layout and Production Machine Maintenance are very influential in the creation of effectiveness in the production activities. This study aims to examine the effect of Production Room Layout and Machine Maintenance on Production Effectiveness at PT. Bintang Usaha Nasional. The population in this study is the number of employees in the production field of PT. Bintang Usaha Nasional as many as 30 people. Data collection techniques used were observation, interviews, questionnaires, and literature study. The statistical analysis method used is Path Analysis with partial hypothesis testing (t-test) and simultaneous (f test). The results of the research show that all independent variables (Production Room Layout and Machine Maintenance) have a significant effect on the effectiveness of production at PT. Bintang Usaha Nasional. The Effect of Production Room Layout and Machine Maintenance on Production Effectiveness is 85.7%, while the remaining 14.3% comes from other variables besides the production room layout and machine maintenance.